Face categorization : the role of race and colour in a multi-racial context - Nadia Mazlan (Nanyang Technological University, 2020)
The other-race effect is known as the tendency for individuals to recognize faces of their own race more easily than that of other races, and there has been robust evidence for this effect. However, contrary to most studies, this effect may not be prevalent in multi-racial societies, where individuals from such societies were found to demonstrate a reduced other-race effect. Research suggests that this may be attributed to more social contact and individuating experiences with individuals from other-races, which helps improve their ability to distinguish other-race faces. Similar to previous studies, the results suggest that Singaporeans do not demonstrate the other-race effect, where no own-race advantage was observed in categorizing own-race faces compared to other-races faces. Interestingly, multiple regression analyses revealed that social contact and individuating experiences were not significant factors in predicting the accuracy of face categorization. However, this lack of significant findings may be due to the questionnaire not being comprehensive enough to fully capture the actual inter-racial experiences participants may have had. The present study also examined the effect of colour on face categorization. Past research suggests that colour information may contribute to face perception, where coloured faces were detected faster. However, its contribution to face categorization is still unclear. From the results, no significant colour advantage was observed, where there were similar average reaction times for the categorization of greyscale and coloured faces. However, a significant interaction was found between face race and colour, suggesting that skin colour information may play a role in face categorization.